Large eddy simulation of natural convection heat transfer and fluid flow around a horizontal cylinder - Ma, Haiteng; He, Li (International journal of thermal sciences, 2021)
Natural convection around a single horizontal cylinder has been extensively studied for heat transfer characteristics, but when coupled with fluid flow, the laminar-to-turbulent transition in buoyant plume poses severe challenge on modelling fidelity and physical interpretability. To address this challenge, this paper conducts detailed verification, validation and analysis of high-fidelity large eddy simulation (LES) for an unconfined horizontal cylinder in water with a Rayleigh number of 8 × 107, complemented by Reynolds-Averaged Navier-Stokes (RANS) computations. To the best of the authors' knowledge, this is the first LES study with acceptable accuracy as validate by experimental data for buoyant plume above a single horizontal cylinder. It is found that LES is far more sensitive to mesh resolution and boundary condition setting than RANS. An alarm is set for the use of periodic condition in LES on lateral boundaries of computational domain due to its inferior accuracy than RANS with transition SST model. The finely-tuned LES with pressure condition on lateral boundaries shows satisfactory agreement with experimental data in terms of heat transfer on cylinder surface and buoyant plume velocity, based on which new physical insight on transitional behavior of thermal plume is obtained. It is found that after leaving the cylinder, buoyant plume is laminar and accelerates, subject to work input from buoyancy force, while its temperature keep decreasing due to heat loss to atmosphere. Flow instability appears first in upward velocity at a streamwise Grashof number of 1.5 × 108, where transition to turbulence onsets. Thermal plume continues to accelerate until it begins to sway horizontally, where energy dissipation into turbulence becomes the major loss mechanism of mean flow energy. Thus, cross-stream diffusivity is augmented notably due to turbulent stresses, leading to smoothing of transverse velocity distribution and reduction of transversely-averaged mean kinetic energy. Transversely-averaged turbulent kinetic energy keeps increasing in transitional regime until the streamwise Grashof number reaches 7 × 109 and then declines to approach an asymptotic value, signifying the end of transition. Overall speaking, buoyancy work dominates the change in mean flow energy, while mean shear outweighs buoyancy in producing turbulent kinetic energy.